Soviet concept of limited Sovereignty from lenin to Gorbachev - Jones, Robert A. (London, 1990)
The book examines the origins, development and contemporary significance of the Soviet doctrine of 'limited sovereignty' ('the Brezhnev Doctrine'), with particular reference to the doctrine's implications for the Soviet Union's relations with Eastern Europe. The author identifies and considers the multiple functions served by the Soviet Union's essentially dualistic or 'bi-axial approach to sovereignty, which embraces notions derived from both general international law and from Soviet Marxist Leninist doctrine. A study of the roles performed by 'legal-positivist' and 'proletarian internationalist' postulates in the Soviet conceptualisation of sovereignty is used as a focus for an analysis of several key aspects of Soviet foreign policy: for example, the dynamic of change in Soviet international relations doctrine; the interplay between Soviet doctrine and policy; and the uses of verbal strategies in international affairs. The book also includes a comparative analysis of the U. S. 'Monroe Doctrine'. The author argues that, although in the Gorbachev era of 'new thinking' the Soviet doctrine of sovereignty may be developing a 'third axis', Western predictions of the imminent or actual demise of the 'Brezhnev Doctrine' are premature.
Keywords: International relations